Sustainability diagnosis of the Company Galix Tech S.A. - QUISPE QUEZADA, URIEL RIGOBERTO (2019)
Objectives. Perform the diagnosis of sustainability of Galix Tech S.A. identifying the current situation, problems and perspectives in the social, ecological and economic dimensions of the operation activities. Materials and methods. The gathering of information has been used through a survey duly formulated with the indicators that reflect averages in the categories indicated. It is a descriptive study, with a quantitative approach, as a tool for the analysis the biogram has been used for the identification of sustainable development, obtaining from the quantitative values the graphic representation of the units of measurement by means of the survey carried out. SAFE software has been used as the main tool in version 1.0, in which maximum and minimum values have been obtained through the variables that have subsequently been analyzed at depth. Results. The results reached within a range of sustainability implementation of 1.94, however there is still dispersion in the environmental and social factors, they must be prioritized to take actions and review the procedures, plans and give continuity to sustainable business level. Conclusions The average values in the (S) reached an average of 2.35 with a degree of improvement that makes it slightly sustainable in aspects of satisfaction of customer requirements and markets, putting more integrity the company with its customers, satisfaction according to the needs of the market, with a variety of products in its portfolio, at level (S2) reached average values of 1.63, which represents a variation in the correlation of activities from the organization, process management and use of its resources in environmental policy, finally the (S3) reached an average of 1.64, this average is insufficient, it requires promoting more efficient social aspects that are in line with sustainability, improving direct dealings with the staff attending to their needs and stimulating benefits according to the  performance and productivity of employees. transparent in communication with greater efficiency.